DESIGN OF MICROCONTROLLER-BASED CUBICLE SUBSTATION CONTROL AND MONITORINGSYSTEM USING LORA MODULE AT THE AIRPORT - Zidan Nasikh, Muhammad; Iswahyudi, Prasetyo; Rochmawati, Laila (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The cubicle is one of the power distribution devices that acts as an input from a voltage source that will be distributed to all airport loads. Currently, cubicle monitoring at airports in Indonesia is still done manually. Thus, when a fault occurs, repairs will take a long time because the exact location of the problem cannot be determined. Therefore, this tool is designed to improve the work efficiency of technicians during repairs for smooth flight operations at the airport. This tool is designed to control, monitor and know if there is a disturbance, especially overload or voltage drop in the cubicle remotely. In this tool design there are 2 tools, namely the transmitter and receiver modules. In the transmitterusing a PZEM 004-T voltage current sensor and an Arduino Uno microcontroller with a lora module as a remote communication. While in the Receiver module this tool is also equipped with a Lora module and NodeMCU Esp32 as awifi module whose data will be displayed through the Blynk Application. In designing this tool in the form of a prototype and the results, if this tool works properly it will provide a warningto the user that there is a disturbance in the cubicle. this tool can effectively increase the technician’s time to complete field repairs